2011
DOI: 10.1371/journal.pone.0021493
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Plasticity Induced by Short-Term Multimodal Musical Rhythm Training

Abstract: Performing music is a multimodal experience involving the visual, auditory, and somatosensory modalities as well as the motor system. Therefore, musical training is an excellent model to study multimodal brain plasticity. Indeed, we have previously shown that short-term piano practice increase the magnetoencephalographic (MEG) response to melodic material in novice players. Here we investigate the impact of piano training using a rhythmic-focused exercise on responses to rhythmic musical material. Musical trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 64 publications
(77 reference statements)
8
87
3
Order By: Relevance
“…The advancement of the last tone by 100 ms was, likewise, very detectable. The temporal change was much higher than the perceptual threshold of 50 ms which we found for the same stimuli in a group of musical novices in an earlier study (Lappe et al, 2011).…”
Section: Subjectscontrasting
confidence: 69%
“…The advancement of the last tone by 100 ms was, likewise, very detectable. The temporal change was much higher than the perceptual threshold of 50 ms which we found for the same stimuli in a group of musical novices in an earlier study (Lappe et al, 2011).…”
Section: Subjectscontrasting
confidence: 69%
“…The influence of musical practice on brain functions and brain plasticity in healthy nonmusician subjects has been demonstrated in previous short-term musical-training studies [86][87][88]. The results of the present study indicated that musical practice influences cortical functions in Tourette subjects and that the practice of well-trained music leads to frequency reduction.…”
Section: Discussionsupporting
confidence: 78%
“…In this context, it is hypothesized that the unisensory representation that is trained lowers the neural threshold needed for the activation of these structures [106] and, as a result, the "downstream" multisensory structures receive enhanced input. This finding is further supported by studies indicating plastic effects due to multisensory training within unisensory processes, such as the studies on the effects of multisensory piano training on auditory processing by Lappe et al [62,63] Multisensory training modifies the unisensory structures, allowing for enhanced unisensory processing, which in turn send their output to the higher-order multisensory regions. B: Multisensory training modifies the feed-forward and feedback connections between the unisensory structures, allowing for better communication between the different modalities.…”
Section: Functional Frameworkmentioning
confidence: 53%
“…playing a musical instrument) and can be easily compared with controls. Short-term music training can be used in a longitudinal setting to compare behavior, brain function and structure before and after an applied training protocol [62][63][64]. This approach allows causal inference regarding the origin of the neuroplastic changes.…”
Section: Multisensory Plasticitymentioning
confidence: 99%
See 1 more Smart Citation